Development of Conceptual Reasoning versus Understanding of Children’s Theory of Mind and Extraordinary (Supernatural) Minds during Middle Childhood - Elżbieta Rydz; Arkadiusz Gut; Anna Pietryga; Zbigniew Wróblewski (Religions, 2023)
It is still not known how a person acquires the ability to think about extraordinary minds. This study examined the point at which a significant distinction appears, the conceptual differentiation of the ordinary mind from the extraordinary mind. Additionally, it examined whether this distance is related to a certain type of conceptual knowledge and understanding of religious concepts. The study involved 117 children from Poland within the age range of 3 to 7 years old (56% girls; 44% boys). The following methods were used: The Deceptive Box Task, The Conceptual reasoning scale from the IDS-P, and the Short test of understanding religious concepts. The obtained results are closer to one of the hypotheses discussed in this area—the anthropomorphism hypothesis, which assumes that after gaining competence in understanding ordinary minds, children begin to build and understand the competencies of extraordinary minds.